(untitled) (Research, Society and Development, 2022)
Background. Mucocele is a benign and asymptomatic pseudo cystic lesion that develops secondarily to the leakage or retention of mucous material from the salivary glands, mainly from the minor salivary glands. Aim. The objective was to assess the available evidence related to the prevalence of oral mucoceles in children and adolescents. Design. Relevant articles were searched in electronic databases of PubMed via MEDLINE, Embase and Scopus. Two review authors independently assessed the risk of bias in the included articles and extracted data. Results. From 638 potentially eligible articles, fifteen relevant articles were included. The overall risk of bias was low for all the studies. All selected studies exhibited appropriate data and were included in the meta-analysis. Regarding publication bias, the statistical analysis did not identify asymmetry in the funnel graph (p=0.867). Conclusion. Considering the global analysis of the included studies, it was found that, the pooled prevalence of mucoceles was 1.77% (CI: 1.19% - 2.65%). It is suggested that future studies consider the classification of the particularities of each clinical presentation of patients seen in dental offices, in order to establish better morphological and anatomical definitions of the lesions concerning mucoceles. Studies that seek to standardize variables - related to age group, time interval, geographic region, genetic formation of the population, examined locations and classification of diseases into subgroups are also important. The certainty of the evidence was considered low.